2016
DOI: 10.1093/mnras/stw1031
|View full text |Cite
|
Sign up to set email alerts
|

The continuing story of SN IIb 2013df: new optical and IR observations and analysis

Abstract: SN 2013df is a nearby Type IIb supernova that seems to be the spectroscopic twin of the well-known SN 1993J. Previous studies revealed many, but not all interesting properties of this event. Our goal was to add new understanding of both the early and late-time phases of SN 2013df. Our spectral analysis is based on 6 optical spectra obtained with the 9.2m Hobby-Eberly Telescope during the first month after explosion, complemented by a near-infrared spectrum. We applied the SYNAPPS spectral synthesis code to con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 120 publications
(225 reference statements)
1
15
0
Order By: Relevance
“…For this reason, we will compare SN 2017ivv to both fast-declining SNe II and SNe IIb with well-sampled light curves and some spectra during both the photospheric and nebular phase. The fast-declining SN II group consists of ASASSN-15oz (Bostroem et al 2019), SN 2014G (Terreran et al 2016), SN 2013ej (Valenti et al 2014;Huang et al 2015;Yuan et al 2016), and SN 2013by (Valenti et al 2015;Black et al 2017), while the SNe IIb sample consists of SN 2015as (Gangopadhyay et al 2018), SN 2013df (Morales-Garoffolo et al 2014;Szalai et al 2016), SN 2011hs (Bufano et al 2014), SN 2011dh (Arcavi et al 2011;Sahu et al 2013;Ergon et al 2014), SN 2008ax (Pastorello et al 2008Taubenberger et al 2011;Modjaz et al 2014), and SN 1993J (Barbon et al 1995;Matheson et al 2000). Because of the extremely low luminosity of the host of SN 2017ivv, we also include SN 2015bs (Anderson et al 2018), which is a slow-declining SN II that exploded in the faintest host galaxy found before SN 2017ivv.…”
Section: Light-curve Evolutionmentioning
confidence: 99%
“…For this reason, we will compare SN 2017ivv to both fast-declining SNe II and SNe IIb with well-sampled light curves and some spectra during both the photospheric and nebular phase. The fast-declining SN II group consists of ASASSN-15oz (Bostroem et al 2019), SN 2014G (Terreran et al 2016), SN 2013ej (Valenti et al 2014;Huang et al 2015;Yuan et al 2016), and SN 2013by (Valenti et al 2015;Black et al 2017), while the SNe IIb sample consists of SN 2015as (Gangopadhyay et al 2018), SN 2013df (Morales-Garoffolo et al 2014;Szalai et al 2016), SN 2011hs (Bufano et al 2014), SN 2011dh (Arcavi et al 2011;Sahu et al 2013;Ergon et al 2014), SN 2008ax (Pastorello et al 2008Taubenberger et al 2011;Modjaz et al 2014), and SN 1993J (Barbon et al 1995;Matheson et al 2000). Because of the extremely low luminosity of the host of SN 2017ivv, we also include SN 2015bs (Anderson et al 2018), which is a slow-declining SN II that exploded in the faintest host galaxy found before SN 2017ivv.…”
Section: Light-curve Evolutionmentioning
confidence: 99%
“…Typical ejecta dust masses reported in SNe younger than day 10,000 are between 10 −6 -10 −3 M (e.g. Sugerman et al 2006;Meikle et al 2007;Kotak et al 2006;Szalai et al 2016) and it has been suggested that the dust masses increase in time (Gall et al 2011(Gall et al , 2014. Because the measurements of late phase dust masses are limited to a few SNe (e.g.…”
Section: Extra-galactic Snementioning
confidence: 99%
“…SN 2013ai shows similar plateauing after 400 days at 4.5 μm to a decline rate of 0.23 mag/100 days, but there is insufficient coverage in the 3.6 μm band. For a detailed discussion of SN 2013df, see Szalai et al (2016). SN 2013am and SN 2011ja (Andrews et al 2016) rebrighten in different epochs.…”
Section: Type II Snementioning
confidence: 99%